Over 20% efficient CIGS-perovskite tandem solar cells - Guchhait, Asim (2020)
The development of high efficiency semitransparent perovskite solar cells is necessary for application in integrated photovoltaics and tandem solar cells. However, perovskite’s sensitivity to temperature and solvents impose a restriction on following processes, thus favoring physical vapor deposition for the transparent contacts. Protection may be necessary, especially for high energy sputtering and a transparent buffer layer providing good electrode adhesion and conductivity is desired. Here we evaluate Ag and MoOx buffer layers in pursuit of high efficiency tandem solar cells. The usage of thin Ag as a buffer layer demonstrated indium tin oxide (ITO) contacts that were resistant to delamination and yielded a 16.0% efficiency of semitransparent perovskite solar cell with average transparency of 12% in visible range and >50% in near-infrared. Further application in tandem with Cu(In,Ga)Se showed an overall efficiency of 20.7% in a 4-terminal (4T) configuration, exceeding the individual efficiencies of the subcells.